Comparative Study of NiTi Orthodontic Wires. (2015) - Fernandes, F.M. Braz; Cruz, J.M.; Magalhães, R.C.A.
Abstract: In this study, two superelastic NiTi orthodontic wires (0.46 x 0.64 mm 2 ) were analyzed. The determination of phase transformation temperatures along with the identification of the predominant phase at room and intraoral temperatures were accomplished by DSC analysis. Superelastic behavior was analyzed through tensile tests. 3-point bending tests were performed on a model design which included brackets to compare wires' behavior: lower forces corresponding to Ormco wires' reverse phase transformation plateau when compared to Dentaurum were exhibited. Wire slippage inside the brackets and friction caused by wire-bracket-ligature combinations on bending and pulling tests, respectively, are also discussed.